2021
DOI: 10.1186/s13049-021-00882-6
|View full text |Cite
|
Sign up to set email alerts
|

Systems for recognition and response to deteriorating emergency department patients: a scoping review

Abstract: Background Assessing and managing the risk of clinical deterioration is a cornerstone of emergency care, commencing at triage and continuing throughout the emergency department (ED) care. The aim of this scoping review was to assess the extent, range and nature of published research related to formal systems for recognising and responding to clinical deterioration in emergency department (ED) patients. Materials and methods We conducted a scoping r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 61 publications
(444 reference statements)
0
2
0
Order By: Relevance
“…For patients presenting without initial physiologic abnormalities, there is no standard framework for predicting subsequent decompensation or care needs [8][9][10] , and unexpected clinical decompensation can arise. Some studies have shown that up to 14.5% of ED patients experience clinical decompensation 11 , with up to 12.9% experiencing unreported decompensation (i.e., development of abnormal vital signs without clinician notification), particularly in overcrowded EDs and among elderly patients 12 .…”
Section: Introductionmentioning
confidence: 99%
“…For patients presenting without initial physiologic abnormalities, there is no standard framework for predicting subsequent decompensation or care needs [8][9][10] , and unexpected clinical decompensation can arise. Some studies have shown that up to 14.5% of ED patients experience clinical decompensation 11 , with up to 12.9% experiencing unreported decompensation (i.e., development of abnormal vital signs without clinician notification), particularly in overcrowded EDs and among elderly patients 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition of, and response to, deteriorating ED patients is primarily an emergency nursing responsibility. Poor patient assessment and reassessment results in unrecognised clinical deterioration or delays to recognition and, or response to deteriorating patients 6. Despite the key role emergency nurses play in patient assessment, reassessment and safety, there is no standardised emergency nursing assessment framework in use for Australia’s 29 000+emergency nurses 7.…”
Section: Introductionmentioning
confidence: 99%